Operating Cost and Treatment of Boron from Aqueous Solutions by Electrocoagulation in Low Concentration - Fatma Deniz; Ceyhun Akarsu (Global Challenges, 2018)
Abstract The objective of this study is to determine the optimum parameters of electrocoagulation process in treatment of boron in low concentrations. Especially, studies on electrode optimization in low boron concentrated waters are insufficient. Therefore, the effect of electrode combination (Al–Al, Al–Fe, Al–SS, Fe–Al, Fe–Fe, and Fe–SS), pH (5–9), current density (8–24 mA cm−2), distance (1–3 cm), and electrolysis time (10–90 min) on treatment of boron containing wastewater is studied to obtain maximum removal efficiency. The maximum removal efficiency of boron is obtained as 95.6%. Operation conditions for maximum removal are the electrode combination of Fe–Al, current density of 16 mA cm−2, pH 7.0, concentration of 30 mg L−1 and the reaction time of 70 min. Operating cost of the electrocoagulation process is calculated as 2.35 $ m−3. This study indicates that the electrocoagulation process can be successfully applied in order to treat boron‐polluted wastewaters at low initial concentrations.